Design and development of honeycomb structured nitrogen-rich cork derived nanoporous activated carbon for high-performance supercapacitors. (February 2021) - Mitravinda, Tadepalli; Anandan, Srinivasan; Sharma, Chandra Shekhar; Rao, Tata Narasinga
Highlights: Synthesis of honeycomb-like structured porous carbon upon chemical activation and subsequent nitrogen doping. Devise a facile and cost-effective route to synthesize carbon with high electrical conductivity, large surface area with narrow pore size distribution. N-rich activated carbon having hierarchical micro to mesoporous framework with a high surface area of 1378 m 2 /g and crystalline carbon. Achieved a high gravimetric capacitance of 133 F/g with less ESR and delivering maximum specific energy of 42 Wh/Kg with a specific power of 750 W/Kg. Retention of 98% of initial capacitance even after 10, 000 cycles at 4 A/g current density. Abstract: Nitrogen-doped nanoporous activated carbon is considered as exciting material for energy storage applications owing to its ordered atomic arrangement and high electrical conductivity. In the present study, we focus on synthesizing cork derived activated carbon (CAC) using bio-waste (cork) by adopting melamine assisted chemical reaction in which three different stoichiometric ratios of cork carbon to melamine are used (1:1, 1:5, 1:10). As synthesized, nitrogen-doped carbons are further activated by a chemical method later to induce porosity. The XRD and Raman spectroscopic measurements revealed the presence of highly ordered graphitic carbon with few-layered graphene-like structure after chemical activation process. among the carbon materials, CAC with a 1:1 (Carbon/melamine) ratio possess a unique honeycomb structure and exhibits a hierarchical micro to mesoporous nature with a high surface area (1378 m 2 /g), large pore volume (0.8 cm 3 /g) and average pore diameter of 3.1 nm. The resulting material with 4.38 wt.% of nitrogen content delivers capacitance of 133 F/g for supercapacitor application and its performance is on par with commercial YP-50F (102 F/g) at a current density of 1 A/g in 1 M TEABF4 /AN between the potential window of 0–3 V. Further it displays an outstanding rate capability (i.e., 65 F/g at 20 A/g) and long cyclic stability (98% capacity retention after 10, 000 cycles) by maintaining a specific energy of 42 Wh/Kg with a specific power of 750 W/Kg. The 3D inter-connected honeycomb-like structure with superior textural parameters (higher-surface area, large pore volumes, hierarchical pores and high graphitic nature) and nitrogen doping significantly contributed to the improved efficiency of CAC for Supercapacitor application. Graphical abstract: Image, graphical abstract